Adaptive Client to Mirrored-Server Assignment for Massively Multiplayer Online Games - Webb, Steven; Soh, Sieteng (SPIE and IS&T, 2008)
The Mirrored Server (MS) architecture for network games uses multiple mirrored servers across multiple locations to alleviate the bandwidth bottleneck and to reduce the client-to-server delay time. Response time in MS can be reduced by optimally assigning clients to their mirrors. The goal of optimal client-to-mirror-assignment (CMA) is to achieve the minimum average client-to-mirror delay considering player joins (CMA-J) and leaves (CMA-L), and mirrors with limited capacity. The existing heuristic solution considers only CMA-J, and thus the average delay of the remaining players may increase when one or more players leave. Furthermore, the solution ignores mirror capacity, which may overload mirrors. In this paper we present a resource usage model for the MS architecture, and formally state the CMA problem. For both CMA-J and CMA-L we propose a polynomial time optimal solution and a faster heuristic algorithm that obtains near optimal CMA. Our simulations on randomly generated MS topologies show that our algorithms significantly reduce the average delay of the existing solution. We also compare the merits of the solutions in terms of their optimality and running time efficiency.